The association of radiographic progression with serum R-spondin 1 (RSPO1) levels or Dickkopf-1 (DKK1)/RSPO1 ratios in rheumatoid arthritis patients: clinical evidence for reciprocal inhibition between DKK1 and RSPO1. (November 2014) - Choi, BY; Chang, SH; Cho, HJ; Kang, EH; Shin, K; Song, YW; Lee, YJ
Abstract : Objectives: To investigate the clinical implications of serum levels of R-spondin 1 (RSPO1), a natural antagonist for Dickkopf-1 (DKK1), and of DKK1/RSPO1 ratios in rheumatoid arthritis (RA) patients. Method: Serum DKK1 and RSPO1 levels were measured in 102 RA patients and 39 age- and gender-matched healthy controls. In addition, DKK1 and RSPO1 levels were determined prior to and 3 months after anti-tumour necrosis factor alpha (anti-TNF-α) therapy in 15 RA patients. Clinical and laboratory data and baseline radiographs of the hands and feet were obtained. Serial radiographs were evaluated in 83 RA patients. Radiographic joint damage was assessed by the modified Sharp/van der Heijde score (SHS). Results: Serum RSPO1 levels were significantly reduced whereas serum DKK1 levels and DKK1/RSPO1 ratios were significantly increased in RA patients compared with controls (all p < 0.0001). Anti-TNF-α treatment significantly suppressed DKK1/RSPO1 ratios (p < 0.01). In contrast to DKK1 or RSPO1 levels, the ratios were significantly associated with erosive disease, elevated acute phase reactants, Disease Activity Score in 28 joints (DAS28) > 3.2, and radiographic progression rate (all p < 0.05). Although the RA patients with radiographic progression exhibited significantly increased DKK1 and reduced RSPO1 levels (p < 0.05), only the DKK1/RSPO1 ratio (log-transformed) was found to be a significant predictor of subsequent radiographic progression [odds ratio (OR) 2.07, p < 0.01]. Conclusions: In this study, the presence of RSPO1 in the circulation was shown for the first time. Our results suggest that the serum DKK1/RSPO1 ratio represents a better predictor of structural progression than either DKK1 or RSPO1 levels alone in RA patients.